Hungary : Technical Assistance Report-Operational Aspects of Establishing an Asset Management Company. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This Technical Assistance report examines Operational Aspects of Establishing an Asset Management Company. In November 2014, the Magyar Nemzeti Bank (MNB) established the Magyar Reorganizacios es Koveteleskezelo (MARK), an asset management company. This step was taken to help restore monetary transmission, credit growth, and economic recovery. The MNB has established MARK on a sound foundation: banks' participation is voluntary, market prices determine valuations, and MARK's lifetime is 10 years. MARK has a clear, well-defined mandate to focus on maximizing the value of its assets. This is supported by an ambitious return on equity and a valuation methodology based on market prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; ISCR; Mark; MNB Representative; Risk Appetite; Hungary